Teaching Black Lives in College When Black Lives Didn’t Matter that Much K through 12 - Trembath, Sarah (Radical Teacher, 2020)
This article explores complexities in teaching Black-authored material (especially Hip Hop lyricism) in premominantly non-Black college composition courses. It uses Barbara Smith's (1978) "Toward a Black Feminist Criticism" as a lens through which to define and examine those complexities. It offers antiracist pedogogal practices and posits withdrawal for reflection and self-care as a viable choice.